2020
DOI: 10.3390/ijerph17155584
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of the Relationship between Motivation for Physical Activity and Emotional and Behavioural Difficulties in Children Aged 8–12 Years: The Role of Autonomous Motivation

Abstract: While motivation for physical activity (PA) and PA participation have been linked, research on the relationship between motivation for PA and mental health outcomes is scant, with studies involving children largely underrepresented. Grounded in self-determination theory, this cross-sectional study aimed to determine whether autonomous motivation versus external motivation (a form of controlled motivation) for PA is associated with fewer emotional and behavioural difficulties and higher levels of PA in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…This includes resilience, sense of competence, self‐esteem, vitality, self‐determination, positive relationships, mood enhancement, self‐efficacy, positive mental health and emotion, worthwhile‐ness, life satisfaction, happiness, mindfulness, and quality of life (QoL) 5,7‐9 . PA has been shown to have a positive relationship with SWB as it can help to meet psychological needs 10 . Additionally, from a neural perspective, it has been proposed that PA may activate the brain in a range of regions (eg, the prefrontal cortex, caudate nucleus, and hippocampus 11,12 ) that are implicated in emotional processing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes resilience, sense of competence, self‐esteem, vitality, self‐determination, positive relationships, mood enhancement, self‐efficacy, positive mental health and emotion, worthwhile‐ness, life satisfaction, happiness, mindfulness, and quality of life (QoL) 5,7‐9 . PA has been shown to have a positive relationship with SWB as it can help to meet psychological needs 10 . Additionally, from a neural perspective, it has been proposed that PA may activate the brain in a range of regions (eg, the prefrontal cortex, caudate nucleus, and hippocampus 11,12 ) that are implicated in emotional processing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…needs. 10 Additionally, from a neural perspective, it has been proposed that PA may activate the brain in a range of regions (eg, the prefrontal cortex, caudate nucleus, and hippocampus 11,12 ) that are implicated in emotional processing. Therefore, PA may be an attractive mechanism to help children adaptively cope when faced with psychological stressors.…”
Section: The Influence Of Pa On Subjective Wellbeingmentioning
confidence: 99%
“…Thus, from a child perspective, meetings with healthcare professionals need to be adapted to them and include alternative and augmentative communication tools in order to be engaging and motivating [27]. When a person's motivation is autonomous, they experience better behavioral outcomes as well as improved wellbeing and mental health [30]. This shows the importance of an individual care plan where the child's interest is included for the child to attain desirable outcomes [24].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study showed that children’s motivation, based on changes in SDT constructs, led to changes in the behaviors associated with PA, and children who maintained high autonomous motivation also had a high level of PA [ 20 ]. Several studies have reported that autonomous motivation strongly correlates positively with MVPA, and a good autonomous motivation can predict a higher level of MVPA in adolescents [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%